Yield and distribution of biomass and nutrients in peach palm cropped under irrigation in the semi-arid area of brazilian Northeast. - DRUMOND, M. A. (1999)
The objective of this paper was to quantify the biomass and the nutrient concentration in the components of the peach palm (Bactris gasipaes H.B.K.).